2019
DOI: 10.1007/s00296-019-04384-8
|View full text |Cite
|
Sign up to set email alerts
|

Moderate-to-high intensity exercise with person-centered guidance influences fatigue in older adults with rheumatoid arthritis

Abstract: Fatigue is described as a dominant and disturbing symptom of rheumatoid arthritis (RA) regardless of the advances in pharmacological treatment. Fatigue is also found to correlate with depression. The objective was to evaluate the impact of moderate-to-high intensity, aerobic and resistance exercise with person-centered guidance on fatigue, anxiety and depression, in older adults with RA. Comparisons were made between older adults (> 65 years) with RA taking part in a 20-week moderate-to-high intensity exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…24,30) It induces IL-10-mediated anti-inflammatory response and IL-1ß inhibition. [23][24] This study confirmed the results of previous studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…24,30) It induces IL-10-mediated anti-inflammatory response and IL-1ß inhibition. [23][24] This study confirmed the results of previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…20) According to a study by the Diabetes Prevention Program (DPP), physical activity and weight loss interventions can reduce the risk of diabetes by 58%. [21][22][23] Physical activity and glycemic control may be beneficial in the inhibition of RA progression as well as in the reduction of its prevalence in patients with prediabetes. 24) However, T. Yates study reported that intensive physical intervention or previous physical activity level did not significantly reduce 2-h post prandial or fasting blood glucose levels 25) in adults with prediabetes and the expression of inflammatory markers 14) in patients with either RA or prediabetes.…”
mentioning
confidence: 99%
“…However, the ESR increased in both groups, which is to be expected with increased age [28]. Exercise is known to possibly slow down the aging of the immune system and diminish the effects of "inflamaging" [29][30][31] but neither in this 4 year follow-up study nor directly after the intervention were any changes of inflammatory markers found [32]. Of all participants 21.3% reported maintained healthenhancing physical activity (including both aerobic and resistance training) for the last 6 months before inclusion in the present study.…”
Section: Discussionmentioning
confidence: 60%
“…For every rated mm (0-100) on VAS fatigue the chance of increasing physical activity over 4 years only decreased by 4%, but with clinically relevant fatigue being defined as VAS > 20 [61], a participant presenting a clinically relevant fatigue at baseline could be considered to be at 56% less chance of increasing LTPAI over 4 years. However, this cohort only showed limited fatigue at baseline and the intervention was found to reduce fatigue [32].…”
Section: Discussionmentioning
confidence: 75%
“…It promotes acute release of anti-inflammatory myokines from skeletal muscle and causes reduction of visceral fat releasing pro-inflammatory adipokines [13,14] thereby it reduces the chronic low-grade inflammation known as inflamm-aging [12]. We have shown that older adults (≥65 years) with RA improve significantly with respect to aerobic capacity and muscle strength, fatigue and patient's global impression of change (PGIC) [15,16] after 20 weeks of moderate-to high intensity aerobic and resistance exercise with personcentred guidance [15].…”
Section: Introductionmentioning
confidence: 99%